# 6x-4(3-2x)=4(x-4)-36

## Simple and best practice solution for 6x-4(3-2x)=4(x-4)-36 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for 6x-4(3-2x)=4(x-4)-36 equation:

6x-4(3-2x)=4(x-4)-36
We move all terms to the left:
6x-4(3-2x)-(4(x-4)-36)=0
We add all the numbers together, and all the variables
6x-4(-2x+3)-(4(x-4)-36)=0
We multiply parentheses
6x+8x-(4(x-4)-36)-12=0

We calculate terms in parentheses: -(4(x-4)-36), so:
4(x-4)-36
We multiply parentheses
4x-16-36
We add all the numbers together, and all the variables
4x-52
Back to the equation:
-(4x-52)

We add all the numbers together, and all the variables
14x-(4x-52)-12=0
We get rid of parentheses
14x-4x+52-12=0
We add all the numbers together, and all the variables
10x+40=0
We move all terms containing x to the left, all other terms to the right
10x=-40
x=-40/10
x=-4

`